Safe And Easy Non-Conventional Therapies For Leucorrhoea - Dadlani, Bharti; Keswani, Jyoti; Guru, Basanti (International Research Journal of Ayurveda & Yoga, 2021)
Leucorrhoea or white discharge is a complaint with which each woman suffers at least once in a lifetime .It refers to the white or yellowish discharge from the vaginal canal in women. It is also a sign of normal reproductive activity in all females and is due to hormonal changes in the reproductive system. But it is also caused due to inflammation and infections of the genito-urinary tract. Although the severe and chronic cases require long term treatment with antibiotics, mild cases can be effectively controlled by non conventional therapies. Along with Ayurveda, it can be treated by diet, yoga, Naturopathy and homeopathic medicines. Leucorrhoea in Ayurveda is known as Shweta pradar is predominantly due to Kapha Dosha and which is a symptom not a disease. Shweta pradar can be treated both by external applications and internal medications as described in literature. In this article an effort has been made to compile all non conventional therapies available to treat Leucorrhea. The nature of this work is review type based on traditional Indian wisdom, the materials were collected from Ayurvedic Samhitas like Charak & Sushruta Samhita, traditional hatha yogic texts like Hatha Pradipika & Gheranda Samhita. The texts books on Gynecology were also reviewed to make the work relevant. Various researches on leucorrhea were reviewed using search engines like Pubmed to assess the efficacy of various interventions used for leucorrhoea.